2021
DOI: 10.4018/joeuc.20210701.oa4
|View full text |Cite
|
Sign up to set email alerts
|

Buying Through Social Platforms

Abstract: Social platforms are currently encountering a set of burning issues: low ad conversion rates, cross-channel free-riding phenomena, lack of monetary incentives to retain premium content creators, etc. Direct purchase behaviors between social platform users (e.g., making a direct purchase through a seller's promotional post) can largely resolve these problems. Therefore, it is imperative to study the factors that influence users' direct purchase behavior. This paper focuses on risk- and trust-related factors, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 72 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…Enterprise Risk Management [8,9]. Risk management must run through all aspects of the enterprise, involve all employees of the enterprise, and be based on effective communication and docking.…”
Section: Application Methods Of Machine Learning Inmentioning
confidence: 99%
“…Enterprise Risk Management [8,9]. Risk management must run through all aspects of the enterprise, involve all employees of the enterprise, and be based on effective communication and docking.…”
Section: Application Methods Of Machine Learning Inmentioning
confidence: 99%
“…These topics converged into social commerce because social media platforms have become a significant factor in the shopping experience, allowing consumers to search for and purchase products through social channels. Social commerce studies in TS3 examined the factors influencing consumers' trust and purchase intention in social commerce (Martínez‐López et al, 2021), including the effects of live streaming (Chandrruangphen et al, 2022). Likewise, Khan et al (2022) identified the reasons for social commerce advertising avoidance and shopping cart abandonment.…”
Section: Science Mapping Results and Discussionmentioning
confidence: 99%
“…Social commerce is categorized as a niche topic, fully developed but less critical for the domain. This is because studies on this cluster focused mainly on its advertising and live‐streaming effects on shopping intention (Chandrruangphen et al, 2022; Khan et al, 2022; Martínez‐López et al, 2021). We believe that social commerce studies should also be examined in the contexts of showrooming, webrooming, and channel shopping behaviors.…”
Section: Science Mapping Results and Discussionmentioning
confidence: 99%
“…Perceived risk as the level of uncertainty experienced by consumers regarding their personal purchase or usage of a product or after using the purchased products (Chao et al 2016). When using a new tool for transactions, most consumers first consider whether the tool is trustworthy and the risks that exist (Martínez-López, et al, 2021). Artificial intelligence as a complex new technology, human-AI interaction in which humans may perceive risks (Glikson, E. 2020).…”
Section: Perceived Risk and Consumer Trust In Ai Chatbotsmentioning
confidence: 99%